Lipid compartments and lipid metabolism as therapeutic targets against coronavirus - Cesar-Silva, Daniella; Pereira-Dutra, Filipe S.; Giannini, Ana Lucia Moraes; Maya-Monteiro, Clarissa M.; de Almeida, Cecília Jacques G. (Frontiers in Immunology, 2023)
Lipids perform a series of cellular functions, establishing cell and organelles' boundaries, organizing signaling platforms, and creating compartments where specific reactions occur. Moreover, lipids store energy and act as secondary messengers whose distribution is tightly regulated. Disruption of lipid metabolism is associated with many diseases, including those caused by viruses. In this scenario, lipids can favor virus replication and are not solely used as pathogens' energy source. In contrast, cells can counteract viruses using lipids as weapons. In this review, we discuss the available data on how coronaviruses profit from cellular lipid compartments and why targeting lipid metabolism may be a powerful strategy to fight these cellular parasites. We also provide a formidable collection of data on the pharmacological approaches targeting lipid metabolism to impair and treat coronavirus infection.